Optimisation of palm stearin, palm kernel oil and soybean oil blends for margarine formulations / Siti Hazirah Mohamad Fauzi - Mohamad Fauzi, Siti Hazirah (2014)
Palm stearin has limited application in natural form because of its high melting point, low plasticity and hence cannot be used directly in margarine production. Palm kernel oil contains short and medium triacylglycerols that can give desired melting characteristics and ensures the stable beta prime (P') polymorph in products. To enhance the PS compatibility, it needs to be blended and/or interesterified with soybean oil to impart desirable properties to the final products. Blends of PS, PKO and SBO at certain proportions were formulated using a mixture design (Design Expert 8.0.4, 2010). All the 10 oil blends were subjected to chemical and enzymatic interesterification. The physicochemical, thermal, polymorphism, microstructural, textural properties and kinetics of isothermal crystallisation were studied. The interesterified (IE) blends had lower slip melting points and solid fat contents due to the randomisation in the TAGs. Interesterification also promotes significant alterations in the microstructural and polymorphism of blends, resulted in smaller crystals with P' form. The hardness of interesterified blends were reduced following the reaction. Interesterification also altered the mechanism of crystallisation kinetics of the blends, depending on the composition and the crystallisation temperatures. The optimisation of interesterified ternary blends for trans-free table (TM) and soft margarine (SM) formulations were conducted through graphical multiple responses in Design-Expert. The CIE and EIE for the TM formulation showed slightly different proportions of PS/PKO/SBO with 50/18/32 and 50/22/28 (w/w), while for SM formulation, both the interesterified blends give the same proportions of 51/0/49 (w/w) of PS/PKO/SBO.